Yield Stability and Disease Incident on Six Tomato Genotypes Under Shading - Ulinnuha, Zulfa; Chozin, Muhamad Achmad; Santosa, Edi (Jurnal Hortikultura Indonesia (JHI), 2019)
Tomato becomes important as under-storey crop in agroforestry in Indonesia. However, farmers claim that there is yield reduction under such system. Hence, six tomato genotypes were planted under 50% reduced sunshine and full sunshine as control using randomized block nested design with genotype as main plot. The study was carried out in December 2016 to March 2017 at Cikarawang Experimental Farm, IPB Bogor. Research aimed to evaluate the production stability of tomato genotypes under shading treatment. Results showed that 50% shading affected tomato production and disease incident. Number of collected-fruit was 15-60% higher under 50% shading except for Apel Belgia and Tora genotypes that tended to decrease. Incident of gemini virus decreased by 80% and its severity decreased by 70% under 50% shading. However, 50% shading reduced tomato yield at rate 24.1% in each harvesting cycle due to a tendency on reduction on individual fruit size, irrespective genotypes. Present study demonstrated that genotype and disease incident determined tomato yield under shading. It needs further evaluation on the cause of low disease infection under 50% shading. Keywords: agroforestry, anthocyanin, disease incident, gemini virus, Solanum lycopersicum